The Values of the Care Economy; Comment on "Ensuring Global Health Equity in a Post-pandemic Economy" - Jennifer Cohen (Kerman University of Medical Sciences, 2023)
Labonté proposes that health equity and environmental sustainability may be best obtained through a care economy. Because a care economy plays a key role in Labonté's formulation, its position in the capitalist political economy, the work it entails, and the workers who do it all merit further reflection. I aim to complement Labonté's editorial by elaborating on care economies and the work of social reproduction. The existing care economy is a structural part of capitalism that largely generates and sustains inequities, reinforcing Labonté's argument that transformation is needed. Transformation could, and should, change the perceived value, status, and material rewards of work in the care economy. I then touch on the policy tools Labonté describes, highlighting how they connect to my broader point: that the care economy is currently an integral, but devalued part of capitalism. For a transformation to take place, raising perceived value, status, and material rewards of caring work and the people who do it must be an explicit policy goal.